Stunting: a multisector challenges and unfinished nutrition agenda - Karyadi, Elvina (Faculty of Medicine, Trisakti University, 2019)
It was a great news that during the President election campaign, both President and Vice President candidates addressed a stunting problem during the debate. It shows that stunting is placed as national priority of nutrition problems. Stunting is part of a wider nutrition crises in Indonesia: wasting, anemia and double-burden of malnutrition. According to the 2018 National Health Survey (RISKESDAS), 30.8 percent of Indonesian children under 5 years of age were stunted (almost 8 million children), 17.7 percent were underweight, 10.2 percent were wasted (low weight-for-height).Â Although the prevalence of stunting declined significantly from the 2013 (37.2%), the stunting rates remain unacceptably high. A child that is wasted faces double the risk of mortality associated with stunting. Even, a child that is both stunted and wasted faces a higher risk. Frequent episodes of wasting increase the risk of stunting. Â